2019
DOI: 10.48550/arxiv.1906.02943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rigidity of the mod 2 families Seiberg-Witten invariants and topology of families of spin 4-manifolds

Abstract: We show a rigidity theorem for the Seiberg-Witten invariants mod 2 for families of spin 4-manifolds. We also give a family version of 10/8-type inequality using this rigidity theorem. As applications, we shall give a new series of non-smoothable topological actions on some 4-manifolds, and also prove the existence of a non-smoothable topological family of 4-manifolds whose fiber, base space, and total space are smoothable as manifolds. As a consequence, it follows that the inclusion map Diff(M ) ֒→ Homeo(M ) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…(2) For comparison, see Theorem 1.4 of [10], in which other non-smoothable families have been detected by a different technique based on 10/8-type inequalities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) For comparison, see Theorem 1.4 of [10], in which other non-smoothable families have been detected by a different technique based on 10/8-type inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…(3) The proofs that E satisfies the first and second conditions are based on [10] and [17] respectively. To prove that E satisfies the third condition, we shall use Corollary 1.3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous paper [3] we showed that there exists a smooth manifold which is realized as the total space of a non-smoothable topological fiber bundle (i.e. a bundle with structure group the homeomorphism group which does not admit a reduction to the diffeomorphism group) with a 4-dimensional fiber.…”
mentioning
confidence: 99%